The Effect of Active Learning and the Role of Parents in Online Learning on Learning Outcomes of Class X Students in Office Administration SMK PAB 2 Helvetia - Tiarni Br Torus; Bambang Sutejo (Outline Journal of Education, 2023)
The purpose of this study was to determine the effect of active learning and the role of parents in online learning on the learning outcomes of class X students in Office Administration SMK PAB 2 Helvetia. the sample used was 57 students taken randomly from 133 students. The results obtained are that there is an influence between learning activity and the role of parents in online learning on the learning outcomes of class X students of Office Administration SMK PAB 2 Helvetia, either partially or simultaneously.